Peran Instruktur Dalam Meningkatkan Kecakapan Hidup Melalui Pelatihan Pembuatan Kerajinan Rotan Pada Warga Belajar Di UPTD Pelatihan Koperasi Samarinda - Niken Sulistiawati; Yudo Dwiyono; Hepy Tri Winarti (LPPM Politeknik Pratama, 2024)
People who lack life skills in the form of skills need instructors to be able to improve and have expertise by providing life skills training in the field of craft making. This research aims to (1) describe the role of instructors in improving life skills through rattan craft training, (2) describe the instructors supporting factors students studying at the Samarinda Cooperative Training UPTD. This study used qualitative research methods. Data collection techniques are carried out by data reduction, data presentation and conclusions. Data validity uses source and technical triangulation techniques. The results of this research show that the Instructor’s Role in Improving Life Skills Through Rattan Craft Training fulfills his role as informator, facilitator, motivator and evaluator well. Apart from that, it shows that there are instructor supporting factors that influence the succes of the training implementation, namely instructors who are competent in the field of rattan crafts and have national certification and adequate facilities to support the smooth process of training activities.